2023
DOI: 10.3390/biomedicines11092408
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Bound Uremic Toxins in Senescence and Kidney Fibrosis

Yi Yang,
Milos Mihajlovic,
Rosalinde Masereeuw

Abstract: Chronic kidney disease (CKD) is a progressive condition of kidney dysfunction due to diverse causes of injury. In healthy kidneys, protein-bound uremic toxins (PBUTs) are cleared from the systemic circulation by proximal tubule cells through the concerted action of plasma membrane transporters that facilitate their urinary excretion, but the endogenous metabolites are hardly removed with kidney dysfunction and may contribute to CKD progression. Accumulating evidence suggests that senescence of kidney tubule ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 154 publications
0
2
0
Order By: Relevance
“…[6] These uremic toxins enter the blood circulation through the damaged intestinal epithelial barrier, potentially activate intestinal mucosal immunity, and induce systemic micro-inflammatory response, which further aggravates kidney damage and ultimately leads to the progression of DKD to ESRD. [7] In particular, TMAO, as a low molecular weight substance, is mostly cleared by the kidneys through glomerular filtration and tubular secretion into urine. As DKD progresses, TMAO continues to accumulate in patients due to a decrease in glomerular filtration rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] These uremic toxins enter the blood circulation through the damaged intestinal epithelial barrier, potentially activate intestinal mucosal immunity, and induce systemic micro-inflammatory response, which further aggravates kidney damage and ultimately leads to the progression of DKD to ESRD. [7] In particular, TMAO, as a low molecular weight substance, is mostly cleared by the kidneys through glomerular filtration and tubular secretion into urine. As DKD progresses, TMAO continues to accumulate in patients due to a decrease in glomerular filtration rate.…”
mentioning
confidence: 99%
“…[5] An increasing amount of research evidence has shown that gut microbiota is closely related to DKD. [6][7][8][9][10] Due to a decrease in glomerular filtration rate in DKD, uremic toxins accumulate in patients' circulation, leading to an imbalance in the gut microbiota. This imbalance leads to an increase in harmful bacteria and a decrease in probiotics, which results in an increase in uremic toxins, such as indoxyl sulfate (IS), p-cresol sulfate (p-CS), trimethylamine, and trimethylamine N-oxide (TMAO), and a decrease in renal protective metabolites, such as short chain fatty acids (SCFAs).…”
mentioning
confidence: 99%